Empathy and Alexithymia in Borderline Personality Disorder: Clinical and Laboratory Measures. - New, Antonia S.; Rot, Marije aan het; Ripoll, Luis H.; Perez-Rodriguez, M. Mercedes; Lazarus, Sophie; Zipursky, Emma; Weinstein, Shauna R.; Koenigsberg, Harold W.; Hazlett, Erin A.; Goodman, Marianne; Siever, Larry J. (Journal of Personality Disorders, 2012)
The authors aimed to understand the role of alexithymia in borderline personality disorder (BPD). A total of 79 BPD patients, 76 healthy controls, and 39 patients with avoidant personality disorder (AVPD) were included. Alexithymia and its influence on interpersonal functioning were assessed. The authors explored group differences in empathy in relation to interpersonal function, and they measured responses to emotional pictures with a computer task in which subjects focused either on the experience of the individual in the picture or the subject's own imagined experience. Patients with BPD and AVPD had higher alexithymia than those in the control group. Patients with BPD had more difficulty identifying their own emotions than patients with AVPD. Patients with BPD reported poorer ability to take the perspective of others, but higher distress; they showed intact 'empathic concern.' Differences in computer task performance were clearest during self-relevant responses to negatively valenced pictures. BPD patients are highly responsive to the feelings of others, but they are impaired in identifying/describing feelings and in taking the perspective of others.